Genetic variation in the dimethylarginine dimethylaminohydrolase 1 gene (DDAH1) is related to asymmetric dimethylarginine (ADMA) levels, but not to endothelium-dependent vasodilation. (August 2013) - Lind, Lars; Ingelsson, Erik; Kumar, Jitender; Syvänen, Ann-Christine; Axelsson, Tomas; Teerlink, Tom
Objectives: Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthase. The breakdown of ADMA is mainly governed by the activity of dimethylarginine dimethylaminohydrolases (DDAHs). We investigated if genetic variation in the DDAH1 and DDAH2 genes were related to ADMA andl -arginine levels, as well as measures of endothelium-dependent vasodilation. Methods: In 1016 70-year-old participants of the population-based Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) study (50% women), we measured endothelium-dependent vasodilation (EDV) using the invasive forearm technique with acetylcholine given in the brachial artery and the brachial artery ultrasound technique with measurement of flow-mediated dilatation (FMD). Plasmal -arginine and ADMA levels were measured by high-performance liquid chromatography and 55 single nucleotide polymorphisms (SNPs) in the DDAH1 and DDAH2 genes were genotyped. Results: Several of the genotypes in the DDAH1 gene were highly significantly related to ADMA levels ( p = 10 −7 at best), but not to thel -arginine levels. No relationships between the genotypes in the DDAH2 gene and ADMA orl -arginine levels were found. None of the DDAH1 genotypes being closely related to ADMA levels were significantly related to EDV or FMD. Neither were any of the DDAH2 genotypes closely related to any of the measurements of vasoreactivity. Conclusion: A close relationship was seen between SNPs in the DDAH1, but not DDAH2, gene and ADMA levels. However, variation in those genes was not related to measures of EDV in this elderly population.